THE DEVELOPMENT OF PROCEDURES TO ANALYSE THE RELATIONSHIPS AMONG SEARCH INTERVIEW TECHNIQUES, INFORMATION GAIN, AND CLIENT SATISFACTION WITH ONLINE BIBLIOGRAPHIC RETRIEVAL SERVICES - Auster, Ethel; Lawton, Stephen B.; Currie, A. Blaine (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF